Health Management System In Planning And Procurement Of Drug At Pitu Community Health Center UPT, Ngawi Regency - Anwar, Khoirul; Kurnia sari, Dhita (Universitas STRADA Indonesia, 2020)
One of the main programs in the Health Center is the treatment program. The treatment program in the Health Center is a form of basic health service that is curative. Medicine is an important element in various health service efforts. Most health service efforts use medicine and the cost used for medicine is a fairly large part of the total health costs. The specific objective of this study was to determine the system of drug procurement study flow at the Pitu Health Center UPT, Ngawi Regency. This study uses a descriptive research method with a qualitative approach that is observational. The results of the study Drug management at the Pitu Health Center through planning, requesting, storing, distributing, destroying, controlling, recording and evaluating. The system used is centralized in the pharmacy room. The drugs issued with the drugs received are only slightly different. So for the need for medicine, it can be said to be met but not optimal. For the need for medicine from time to time, it varies according to the needs in the field Drug dispensing system First Expired First Out (FEFO) system, drugs that are close to ED are issued first. First In First Out (FIFO) system, drugs that enter first are issued earlier. There are 2 types of drug planning and procurement systems from GFK according to the stock of drugs available at the DINKES and through BLUD fund spending. Supervision is carried out both at the Pitu Health Center and in the field through usage reports. Keywords: Drugs, Planning and Procurement, Health Centers.